To calculate the speed of the dog relative to the ground, we use the formula,
[tex]v_{dog,ground} = v_{dog, belt} + v_{belt, ground}[/tex]
Here, [tex]v_{dog,ground}[/tex] is velocity of dog with respect to ground, [tex]v_{dog, belt}[/tex] is velocity of dog with respect to belt and [tex]v_{belt, ground}[/tex] velocity of belt with respect to ground.
Given , [tex]v_{dog, belt} = -8 m/s[/tex] and [tex]v_{belt, ground} = 2 m/s[/tex].
Substituting these values in above equation, we get
[tex]v_{dog,ground} = (-8 m/s) + 2m/s = -6 m/s[/tex]